The interferon receptor-1 promoter polymorphisms affect the outcome of Caucasians with HBeAg-negative chronic HBV infection - Karamitros, T; Papatheodoridis, G; Dimopoulou, E; Papageorgiou, M; Paraskevis, D; Magiorkinis, G; Sypsa, V; Hatzakis, A (Wiley, 2015)
The outcome of HBeAg-negative chronic hepatitis B virus (HBV) patients who may remain in the inactive carrier state (IC) or progress to HBeAg-negative chronic hepatitis B may be affected by the host genetic profile. Genetic polymorphisms within not only the promoter but also the coding sequence of the interferon receptor 1 (INFAR1) gene have been associated with susceptibility to chronic HBV infection, but their role on the outcomes of HBeAg-negative patients has not been evaluated. We examined the association of INFAR1 promoter polymorphisms with the phase of chronic HBV infection in a demographically characterized Caucasian cohort of 183 consecutive HBeAg-negative chronic HBV patients.Using a combination of conventional and allele-specific polymerase chain reactions, bidirectional sequencing and DNA-fragment analysis, we performed typing of three Single Nucleotide Polymorphisms (SNPs -568G/C, -408C/T, -3C/T) and one Variable Number Tandem Repeat [VNTR -77(GT)n] within the INFR1 promoter sequence.The genetic polymorphisms examined were found to be associated with the phase of HBeAg-negative chronic HBV patients. Using a multiple logistic regression model adjusting for age, gender and origin of the individuals, we found that patients with linked genotypes -408CT_-3CT were more likely to be ICs (OR = 2.42 vs. CC, P = 0.036). Also, given the partial linkage between SNP -568G/C and VNTR -77(GT)n, we found that linked genotypes -77(GT)n ≤ 8/≤8_-568GC and -77(GT)n ≤ 8/≤8_-568CC were detected more frequently among ICs (OR = 11.69, P = 0.005 and OR = 7.56, P = 0.001 vs. -77(GT)n >8/>8_-568GG respectively).These findings suggest that these genetic variations represent important factors associated with the clinical phase of HBeAg-negative chronic HBV infection.